2016
DOI: 10.4269/ajtmh.15-0866
|View full text |Cite
|
Sign up to set email alerts
|

Zika Virus Emergence and Expansion: Lessons Learned from Dengue and Chikungunya May Not Provide All the Answers

Abstract: Abstract. Following the emergence of Zika in the past decade, there are lessons to be learned from similar emergence events of dengue (DENV) and chikungunya (CHIKV). Specifically, as Zika emerges in the Americas there is a natural tendency to apply the knowledge base of DENV and CHIKV to mitigation and control of a virus with such a similar transmission system. However, there are marked differences that may preclude such broad stroke application of this knowledge base without making potentially faulty assumpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
11

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 31 publications
(43 reference statements)
0
43
0
11
Order By: Relevance
“…Thus vector transmission may have a shorter infectious period than sexual transmission. Recovery after infection seems to confer long-term immunity for individuals [22]. There currently exist no cure, no treatment, and no vaccine for ZIKV.…”
Section: Methodsmentioning
confidence: 99%
“…Thus vector transmission may have a shorter infectious period than sexual transmission. Recovery after infection seems to confer long-term immunity for individuals [22]. There currently exist no cure, no treatment, and no vaccine for ZIKV.…”
Section: Methodsmentioning
confidence: 99%
“…This came as a surprise, as since its first isolation in 1947 in the Zika forest in Uganda [5], the virus was associated with benign disease and had remained mostly unnoticed. Isolated outbreaks have been reported before in Africa and Asia/Oceania but all of them involved small populations [6]. In Brazil Zika virus (ZIKV)…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Krystosik et al ( 22 ) estimated the combined risk for dengue, Zika, and chikungunya but did not provide disease-specific risk estimates; Costa et al ( 35 ) found associations in the spatial distribution of dengue, Zika, and chikungunya but did not use the information on the diseases’ association to improve the accuracy of the risk estimates. The special characteristics of the joint modeling of cocirculating arboviruses provide an epidemiologic tool for transmission control and disease mitigation ( 36 ). …”
Section: Discussionmentioning
confidence: 99%